2003
DOI: 10.1007/bf03018373
|View full text |Cite
|
Sign up to set email alerts
|

Design of oxygen delivery systems influences both effectiveness and comfort in adult volunteers

Abstract: P Pu ur rp po os se e: : The aim of this investigation was to compare the efficiency of four oxygen delivery systems in healthy volunteers. M Me et th ho od ds s: :The subjects received oxygen at flow rates of 3.0 and 5.0 L·min -1 via a face mask, nasal cannulae, and two kinds of new open-and microphone-type oxygen delivery systems (OxyArm™ and Mike Cannula) in a random sequence, and values of partial arterial pressures of oxygen (PaO 2 ) were measured. The comfort of these devices was also evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…13,17,18 Face mask may cause discomfort, induce claustrophobia, and impede oral intake and communication. 19 Nasal mask requires patent nasal passages and mouth closure to minimize leak, and can cause pressure sores and tissue necrosis over the nasal bridge. 20 Collectively, these problems may cause poor adherence to therapy 17 and increased nursing time.…”
Section: Discussionmentioning
confidence: 99%
“…13,17,18 Face mask may cause discomfort, induce claustrophobia, and impede oral intake and communication. 19 Nasal mask requires patent nasal passages and mouth closure to minimize leak, and can cause pressure sores and tissue necrosis over the nasal bridge. 20 Collectively, these problems may cause poor adherence to therapy 17 and increased nursing time.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that perioperative oxygen delivery reduces wound infection and the incidence of nausea andvomiting as well as hypoxemia (Laurer & Gombkoto 2006). Oxygen is generally delivered to patients via oxygen masks or nasal cannulae (Sasaki et al. 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, this study was performed using the OxyArm, in which the diffuser was placed in a plastic boom connected to a headset, and measurements were obtained in healthy volunteers (3). Subsequent work evaluating the diffuser technology used either healthy volunteers, nonoxygendependent patients, or patients with chronic obstructive pulmonary disease of unknown severity, and did not evaluate the diffuser while placed in a face mask (4)(5)(6)8,9). These differences in patient population and interface design may limit the application of earlier findings to patients with chronic, severe respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
“…We studied this hypothesis by titrating supplemental oxygen in oxygen-dependent patients through an OxyMask and Venturi mask (Hudson RCI, USA) in a randomized, single-blind, cross-over design. Although the diffuser technology has been evaluated previously, this has predominantly been in healthy volunteers (3)(4)(5), in which the diffuser was placed in a plastic boom connected to a headset (OxyArm, Southmedic Inc). Only one previous investigation has used the OxyArm in oxygen-dependent patients (6).…”
mentioning
confidence: 99%